Optimizing culturing conditions in patient derived 3D primary slice cultures of head and neck cancer - Greier, Maria do Carmo; Runge, Annette; Dudas, Jozsef; Carpentari, Lukas; Schartinger, Volker Hans; Randhawa, Avneet; Mayr, Melissa; Petersson, Monika; Riechelmann, Herbert (Frontiers in Oncology, 2023)
Abstract Three-dimensional primary slice cultures (SC) of head and neck squamous cell carcinomas (HNC) are realistic preclinical models. Until now, preserving structure and viability ex vivo for several days has been difficult. The aim of this study was to optimize cultivation conditions for HNC SC and analyze the added effects of platelet rich fibrin (PRF) on these conditions. Methods: SC were prepared from the tumor biopsies of 9 HNC patients. Cultures were incubated for 1 and 7 days in three different media- Keratinocyte serum-free medium (SFM), RPMI-1640i, and 1:1 mix of both, with and without addition of PRF. After culturing, SC were fixated, embedded, and stained with Hematoxylin-Eosin (HE) and cleaved caspase-3. In addition, triple immune fluorescence staining for cytokeratin, vimentin and CD45 was performed. Outcome parameters were cell count and cell density, viability and apoptosis, SC total area and proportions of keratinocytes, mesenchymal and immune cells. The effects of culture time, medium, and addition of PRF were calculated in an SPSS generalized linear model and using the Wald Chi-Squared test. Results: Ninety-four slice cultures were analyzed. Viability remained stable for 7 days in culture. After addition of PRF, cell viability increased (p=0.05). SC total area decreased (0.44±0.04 mm2 on day 1 (95% CI: 0.35 to 0.56) to 0.29±0.03 mm2 on day 7 (95% CI: 0.22 to 0.36), but cell density and cell proportions remained stable. Differences in cultivation media had no significant impact on outcome parameters. Conclusion: HNC SC can be preserved for up to 7 days using the tested cultivation media. Cell viability was best preserved with addition of PRF. HNC SC are a versatile experimental tool to study physiology and drug actions. Autologous PRF can help simulate realistic conditions in vitro.